Ação, paixão e estesia em contos de Clarice Lispector - Ferreira, Grazielle de Almeida (2018)
This dissertation analyzes, based on the theoretical instrumental of the French Semiotics, the short stories “Felicidade Clandestina”, “Restos do Carnaval” e “Os desastres de Sofia”, by Clarice Lispector which were published in the book Felicidade Clandestina. In this book, from 1971, the author puts together several short stories written throughout her life. On the whole, Clarice Lispector´s work sets forth intimist characteristics, privileging the human being, with his inquiries and existential crisis. In the texts that constitute the corpus of our research the enunciator projects narrators on the present of the enunciated enunciation who, when submitted to their stream of consciousness; remember important events of their life in the transition from the boyhood to the adolescence. The work, through qualitative and comparative analysis, aimed to examine the discursive strategies used in the construction of female actors, protagonists of each of the narratives, all girls, who face events that lead to an internal transformation. For this, we used elements of the generative path of meaning, with emphasis on the narrative and discursive level of the texts, as well as the concept of passion in semiotics and the notion of event and aesthesis,according to Algirdas Julien Greimas' work Da imperfeição and yet analyzing the way their state of mind are put together. In this way, the theoretical reflexions are used about the concept of passion according to the semiotics and also the notion of event and aesthesia according to the work Da imperfeição, by Algirdas Julien Greimas, with the aim of apprehending the way in which the enunciator constructs the profile of the female actors, protagonists of the stories. As a result, we noted that among the strategies used by the enunciator in the construction of the actors, stand out the theme of an existential order which is associated to the process of female maturation in the passage from childhood to adolescence and is related to aesthetic event that erupts in daily life of these actors and involves suffering and beauty intrinsically amalgamated.